2003
DOI: 10.1097/01.ede.0000072107.90304.01
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin Emissions from a Solid Waste Incinerator and Risk of Non-Hodgkin Lymphoma

Abstract: Although emissions from incinerators are usually not regarded as an important source of exposure to dioxins compared with other background sources, our findings support the hypothesis that environmental dioxins increase the risk of non-Hodgkin lymphoma among the population living in the vicinity of a municipal solid waste incinerator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 19 publications
4
46
0
1
Order By: Relevance
“…It is presently unclear whether exposure to TCDD can lead to sustained Pax5 elevation in B cells and their precursors (Gaidano et al, 2003). Nevertheless, the findings by Krenacs et al (1998) are intriguing in light of several epidemiological studies reporting a positive, although in most cases a weak, association between non-Hodgkin's lymphomas and exposure to certain classes of chemicals including phenoxyacetic acids, chlorophenols, dioxins, dibenzofurans, and polychlorinated biphenyls (Rothman et al, 1997;Hardell et al, 1998;Viel et al, 2000;Floret et al, 2003;Engel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is presently unclear whether exposure to TCDD can lead to sustained Pax5 elevation in B cells and their precursors (Gaidano et al, 2003). Nevertheless, the findings by Krenacs et al (1998) are intriguing in light of several epidemiological studies reporting a positive, although in most cases a weak, association between non-Hodgkin's lymphomas and exposure to certain classes of chemicals including phenoxyacetic acids, chlorophenols, dioxins, dibenzofurans, and polychlorinated biphenyls (Rothman et al, 1997;Hardell et al, 1998;Viel et al, 2000;Floret et al, 2003;Engel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent population-based case-control study was conducted in the same geographical area, and an OR of 2.3 (95% CI: 1.4-3.8) was reported for individuals in the high dioxin exposure category. 163 Lampi et al 135 reported a significantly positive association with NHL risk in a Finnish community whose water system was contaminated with chlorophenols (RR 5 2.8, 95% CI: 1.4-5.6). Individual exposure measurements were not available in these studies.…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 99%
“…Our team first detected a cluster of NHL in an area surrounding an MSWI with high levels of dioxin emissions (Besançon, France) (Viel et al, 2000). Subsequently, an increased risk (odds ratio [OR] = 2.3, 95% confidence interval [CI] 1.4 to 3.8) of NHL was associated with residence under the plume of this MSWI (Floret et al, 2003). These findings have recently been replicated at the national level with a similar exposure assessment approach (Viel et al, 2008).…”
Section: Introductionmentioning
confidence: 84%